The link between firm-level innovation and aggregate productivity growth: a cross-country examination - Almas Heshmati; Hans Lööf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper investigates whether failure in innovation at the firm level can account for cross-country heterogeneity in manufacturing productivity growth. There is no strong evidence in the literature on the existence of such link. Our work, however, differs in a number of ways from much of the previous cross-country comparisons on the relationship between innovation and productivity using firm-level data. First, a broader definition of innovation input is used in which research and development is one of several sources of innovation. Second, a quantitative innovation output measure is used in the analysis. Third, the analysis is based on larger and more representative samples of firms including small firms. Finally, an econometric framework based on the knowledge production function accounting for both selectivity and simultaneity bias is employed. The results from Nordic countries show that given difficulties in pooling the data, it is important to specify country-specific models accounting for country-specific effects and differences in the countries national innovation systems.
Keywords: L60; C51; O31; O32; D24; 330; community innovation; cross-country comparisons; manufacturing; productivity; Innovation; Arbeitsproduktivität; Schätzung; Vergleich; Nordeuropa